CALCULATION OF OFFCENTRALLY COMPRESSED ELEMENTS - Yaremenko, OLENA; Balduk, PAVLO (Herald of Khmelnytskyi National University. Technical sciences, 2022)
A large number of calculation formulas have been proposed to describe the deformation diagrams of masonry and concrete. The data indicate the possibility and expediency of using full masonry deformation diagrams to calculate the strength and deformations of stone and reinforced stone pillars. Experimental samples and stone pillars were tested. The samples were of five types and differed among themselves in the location of reinforcement and the reinforcement ratio, as well as in the method of loading - axial or off-center compression with different eccentricity.In the paper, experimental and calculated longitudinal deformations of masonry and reinforcement for samples of different groups. These data testify to the possibility and expediency of using full masonry deformation diagrams to calculate the strength and deformations of stone and reinforced stone pillars. As the amount of reinforcement in the stretched zone increases, most of the section works on the descending branch of the diagram. The size of the compressed zone increases, which is equivalent to a decrease in eccentricity. Reinforcement of the compressed zone with reinforcement increases the strength of sections with double reinforcement. The shapes of the stress profiles in the masonry practically do not depend on the presence of compressed reinforcement.The calculation establishes the expediency of the installation and the degree of saturation of the stretched and compressed cross-sectional areas with reinforcement.At small eccentricities, when the force is applied within the core of the section, saturation of the compressed zone with reinforcement leads to a noticeable increase in the strength of the section. At large eccentricities, saturation of the compressed zone with reinforcement is ineffective.
Keywords: deformation diagrams; masonry; concrete; axial compression; eccentric compression